Efektivitas Asean Agreement On Transboundary Haze Pollution (AATHP) dalam Penyelesaian Sengketa Kabut Asap antara Indonesia, Malaysia dan Singapura Tahun 2025 - Esther Setianingrum (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Transboundary haze resulting from forest and land fires in Indonesia remains a regional environmental issue. This study analyzes the dispute settlement mechanisms within the ASEAN Agreement on Transboundary Haze Pollution (AATHP) and evaluates their effectiveness regarding the 2025 haze incident. Employing a normative legal research method, the study utilizes statutory, conceptual, and case-based approaches grounded in legal theory. The findings indicate that Article 27 of the AATHP provides only for consultation and negotiation, lacking any binding enforcement mechanism. Consequently, the AATHP has proven ineffective due to weaknesses in its legal substance and institutional structure, as well as an ASEAN legal culture rooted in the principle of non-interference.